(untitled) (Journal of Bangladesh Academy of Sciences, 2013)
The study was conducted to compare the performance of chickens of non-descript desi (ND), hilly (H) and naked neck (NN) genotypes. Data were analyzed by GLM procedure of SPSS in a CRD. The highest hatchability was found in third hatch of ND (86.38%). The chick weight was influenced (p < 0.05) by the egg weight. The average initial body weight of day-old chicks differed significantly (p < 0.001) by genotypes. The lowest and highest mean body weight gain per bird were recorded for ND (329.38 ± 3.32 g) and NN (351.56 ± 5.08 g) genotypes, which indicated that there were an average daily growth rate of 5.88 ± 0.05 and 6.27 ± 0.09 g per bird per day at their 8th weeks growth phases, respectively. Calculated heritability for 12th week body weight of ND, H and NN were 0.16±0.39, 0.50±0.05 and 0.73±0.25, respectively and for 16th week body weight of H and ND were 0.72±0.15 and 0.35±0.15, respectively. Naked neck is genetically superior to non-descript Desi and Hilly in terms of productive and reproductive parameters. DOI: http://dx.doi.org/10.3329/jbas.v37i1.15685 Journal of Bangladesh Academy of Sciences, Vol. 37, No. 1, 93-101, 2013